Efektivitas Anggaran Belanja Desa dalam Peningkatan Pembangunan Manusia (Studi Analisis di Desa Sepahat, Kec. Bandar Laksamana) - Husni Mubarak; Nuraini Nuraini (Jurnal IAKP: Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2021)
This research purposed to determine the effectiveness of village budget absorption and the constraints faced in achieving human development in Sepahat Village. This research is qualitative descriptive carried out in the Bandar Laksamana sub-District in Sepahat Village. Data collection was conducted out by interview, observation and documentation. Results of this research is, based on the measurement of effectiveness, the effectiveness of the village budget in increase human development in Sepahat Village with the highest effectiveness in 2019, namely 96% with the effective category, while the effectiveness was the lowest occurred in 2017, namely only 57% of the budgeted category was not effective and for 2018 the effectiveness of the village budget in increasing development. The number of people in Sepahat Village was higher than in 2017 and lower than the year 2019, which is 80% with a fairly effective category. So it can be said that the effectiveness of the village budget in improving human buildings in Sepahat Village has increased every year. The obstacles faced in human development in Sepahat Village are the first lack of disbursement of village funds, limited availability of facilities, and supervision of the village government. For the next Researchers are then expected to be able to measure what factors and efforts have been made so as to make significant changes.